PERJUANGAN IBU TUNGGAL MENGHADAPI PERUBAHAN PERAN DALAM MEMENUHI KEBUTUHAN ANAKNYA - Assyfa Wahida Rachman; Audina Rismayanti Fadlillah; Dwi Nalendra Rucitra (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
A single mother is a woman who is married and has children, but has been abandoned by her husband due to divorced life or divorced death. This study aims to describe the struggle of a single mother in meeting the needs of her child after a change in role in her family. This study also explains the problems faced by single mothers in meeting the needs of their children. The method used in this study is a qualitative method with a phenomenological approach. This research was conducted by means of observation and interviews. There were two subjects in this study, namely Mrs. D and Mrs. N. Both subjects are single mothers due to the death of their husbands. Mrs. D and Mrs. N struggle alone to meet the needs of their children. Mrs. D faces more difficulties in raising her children, while Mrs. N has more difficulties economically. Both subjects had experienced a downturn at the beginning of being a single mother. This study uses Talcott Parson's theory of structural functionalism theory. This theory is used in analyzing the changing role of a mother after becoming a single mother